Lead detoxification of edible fungi Auricularia auricula and Pleurotus ostreatus: the purification of the chelation substances and their effects on rats - Zhang, Weiwei; Zheng, Xiaojie; Chen, Xiangdong; Jiang, Xuezhen; Wang, Hexiang; Zhang, Guoqing (Frontiers in Nutrition, 2023)
Lead is a global pollutant that causes widespread concern. When a lead enters the body, it is distributed throughout the body and accumulates in the brain, bone, and soft tissues such as the kidney, liver, and spleen. Chelators used for lead poisoning therapy all have side effects to some extent and other drawbacks including high cost. Exploration and utilization of natural antidotes become necessary. To date, few substances originating from edible fungi that are capable of adsorbing lead have been reported. In this study, we found that two commonly eaten mushrooms Auricularia auricula and Pleurotus ostreatus exhibited lead adsorption capacity. A. auricula active substance (AAAS) and P. ostreatus active substance (POAS) were purified by hot-water extraction, ethanol precipitation from its fruiting bodies followed by ion exchange chromatography, ultrafiltration, and gel filtration chromatography, respectively. AAAS was 3.6 kDa, while POAS was 4.9 kDa. They were both constituted of polysaccharides and peptides. The peptide sequences obtained by liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) proved that they were rich in amino acids with side chain groups such as hydroxyl, carboxyl, carbonyl, sulfhydryl, and amidogen. Two rat models were established, but only a chronic lead-induced poisoning model was employed to determine the detoxification of AAAS/POAS and their fruiting body powder. For rats receiving continuous lead treatment, either AAAS or POAS could reduce the lead levels in the blood. They also promoted the elimination of the burden of lead in the spleen and kidney. The fruiting bodies were also proved to have lead detoxification effects. This is the first study to identify new functions of A. auricula and P. ostreatus in reducing lead toxicity and to provide dietary strategies for the treatment of lead toxicity.